Strategies for Determining the Dividend Payout Ratio in Family Firms: An Ethnographic Analysis of Generation Z Preference Shifts - Dewa Putu Yohanes Agata L. Sandopart (Varied Knowledge Journal, 2023)
This study aims to deeply understand how dividend payout ratio determination strategies in family firms are influenced by intergenerational preference shifts, with a specific focus on the entry of Generation Z into the ownership and management structure of family firms. The research employs a qualitative approach with an ethnographic case study design on two family firms listed on the Indonesia Stock Exchange (PT XXX and PT YYY). Data collection was conducted through in-depth interviews with 24 informants, participant observation, and document analysis covering the 2018–2022 period. Data analysis was conducted through domain, taxonomic, componential, and cultural theme analysis to capture patterns of meaning within the data. The research reveals significant shifts in dividend preferences across generations, where founder generations tend to retain earnings for reinvestment with a long-term orientation, Generation X and Millennials demonstrate more balanced preferences between dividends and retained earnings, and Generation Z exhibits distinct characteristics, including higher dividend preferences, stronger demands for transparency, a tendency to question traditional authority, and the use of technology in monitoring dividend policies. These shifts create new tensions in family firm governance that remain underexplored in existing literature. This study contributes by explicitly analyzing the influence of Generation Z's entry on dividend policy in family firms using an ethnographic approach and by integrating the socio-emotional wealth perspective with generational theory.